Global variation in the prevalence of bullying victimisation amongst adolescents: Role of peer and parental supports. (March 2020) - Biswas, Tuhin; Scott, James G.; Munir, Kerim; Thomas, Hannah J.; Huda, M. Mamun; Hasan, Md. Mehedi; David de Vries, Tim; Baxter, Janeen; Mamun, Abdullah A.
Summary: Background: Bullying victimisation is a global public health problem that has been predominantly studied in high income countries. This study aimed to estimate the population level prevalence of bullying victimisation and its association with peer and parental supports amongst adolescents across low and middle income to high income countries (LMICHICs). Methods: Data were drawn from the Global School-based Student Health Survey of school children aged 12–17 years, between 2003 and 2015, in 83 LMICHICs in the six World Health Organization (WHO) regions. We estimated the weighted prevalence of bullying victimisation at country, region and global level. We used multiple binary logistic regression models to estimate the adjusted association of age, gender, socioeconomic status, and parental support and peer support, and country level variables (GDP and government expenditure on education) with adolescent bullying victimisation. Findings: Of the 317, 869 adolescents studied, 151, 036 (48%) were males, and 166, 833 (52%) females. The pooled prevalence of bullying victimisation on one or more days in the past 30 days amongst adolescents aged 12–17 years was 30·5% (95% CI: 30·2–31·0%). The highest prevalence was observed in the Eastern Mediterranean Region (45·1%, 44·3–46·0%) and African region (43·5%, 43·0–44·3%), and the lowest in Europe (8·4%, 8·0–9·0%). Bullying victimisation was associated with male gender (OR: 1·21; 1·11–1·32), below average socio-economic status (OR: 1·47, 1·35–1·61), and younger age (OR: 1·11, 1·0–1·24). Higher levels of peer support (0·51, 0·46–0·57), higher levels of parental support (e.g., understanding children's problems (OR: 0·85, 0·77–0·95), and knowing the importance of free time spent with children (OR: 0·77, 0·70–0·85)), were significantly associated with a reduced risk of bullying victimisation. Interpretations: Bullying victimisation is prevalent amongst adolescents globally, particularly in the Eastern Mediterranean and African regions. Parental and peer supports are protective factors against bullying victimisation. A reduction in bullying victimisation may be facilitated by family and peer based interventions aimed at increasing social connectedness of adolescents.